Experimental Modeling and Evaluation of Solar Cooker For Malaysia Potential - Aman Zaharil, Muhammad Hafiz Osman (IRC, 2016)
The ever increasing demand for energy has causes an energy consumption that is very high and most of the energy used is from a non-renewable energy source. Sun is a great source of energy that is not only free but is renewable and does not cause pollution. Cooking is an important part of everyone’s daily life because food is essential to everybody. Unfortunately many cooker in the market uses electricity and very few of them take advantage of the sun natural energy. In the present study, an attempt has been carried out to design, fabricate and evaluate a locally made solar cooker. The evaluation was performed experimentally. The objective of the experiment was done by experimental modelling and by using mathematical equation to determine some parameters, and eventually finding its efficiency. This experiment is to determine the suitability of a homemade low cost parabolic and box type solar cookers by measuring their efficiency by under Malaysia weather.